Filogeografia comparada de espécies de Trinomys (Rodentia: Echimyidae) na região central da Mata Atlântica - Agrizzi, Juliander (2012)
Echimyidae spiny rats are the most diverse family among hystrichognath rodents from both taxonomic and phenotypic perspectives. In this family, Trinomysspecies are restricted to eastern Brazil, and their distribution is associated with the Atlantic Forest. Data from the literature suggest that the extensive intraspecific variation in this genus makes the task of allocating museum specimens to the 13 currently described species very difficult. Most of the studies on this genus are based on phenotypic traits and those that included molecular analyses examined a few genes or a small number of specimens. The goal of the present paper is to identify and compare the geographical structure of the genetic diversity in populations of three Trinomys species, T. paratus, T. panama, and T. setosus, which occur in the central region of the AtlanticForest. We sequenced and analyzed the mitochondrial cytochrome b (cytb) gene and the nuclear von Willebrand Factor gene (vWF) of 103 specimens. The concatenated gene phylogeny confirmed the monophyly and the high level of sequence divergence among the three species. We identified two diverging phylogroups in T. setosus and in T. panama, well supported in different analyses, indicating that these phylogroups are distinct taxonomic units. According to our molecular dating, the diversification of the lineages leading to these the three species of Trinomys must have occurred in the Upper Miocene, while intraspecific diversification took place mainly in the Pliocene and Pleistocene. The haplotype networks indicated that populations of the three Trinomysspecies are geographically structured in the central region of the Atlantic Forest. Cytb haplotype networks were geographically more structured than vWF networks, suggesting that females of these species have smaller home ranges and do not disperse as far as males do, because mitochondrial DNA is maternally inherited. Populations of both T. setosus and T. panema do not share cytb haplotypes, show isolation by distance and no evidence of recent demographic expansion. The opposite was observed in T. paratus, in which most specimens analyzed were from nearby, lowland regions, facilitating gene flow and, therefore haplotype sharing.